2014
DOI: 10.1080/15481603.2014.883209
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of wood volume and height of olive tree plantations using airborne discrete-return LiDAR data

Abstract: The aim of this study is to analyze methodologies based on airborne LiDAR technology of low pulse density points (0.5 m -2 ) for height and volume quantification of olive trees in Viver (Spain). A total of 29 circular plots of radius 20 m were sampled and their volumes and height were obtained by dendrometric methods. For these estimations several statistics derived from LiDAR data were calculated in each plot. Regression models were calculated to predict volume and height. The results showed a good performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Based on this information, structural parameters of vegetation such as dominant height, carbon stocks and stand crown biomass may be derived [8e10] as well as other indirect parameters such as residual biomass and volume [11,12]. While many successful applications have been reported in forestry using airborne LiDAR systems [13e15], few studies have been found in agriculture [16]. These authors estimated the mean volume and height of olive trees per plot using LiDAR data of low point density (0.5 m À2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this information, structural parameters of vegetation such as dominant height, carbon stocks and stand crown biomass may be derived [8e10] as well as other indirect parameters such as residual biomass and volume [11,12]. While many successful applications have been reported in forestry using airborne LiDAR systems [13e15], few studies have been found in agriculture [16]. These authors estimated the mean volume and height of olive trees per plot using LiDAR data of low point density (0.5 m À2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Forests are an important natural resource which play a significant role in modulating stores and fluxes of water and carbon, maintaining ecological diversity, and regulating climate on the Earth's surface, and provides timber and other forest products constantly which are closely related to humans [1][2][3]. Parameters of individual trees, such as tree location, tree species, tree height, diameter at breast height (DBH), and crown diameter, are vital for sustainable and precise forest management [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, light detection and ranging (LiDAR) has become an increasingly popular tool for forest monitoring and vegetation mapping tasks for its capacity of obtaining the spatial distribution of surface characteristics with dense point clouds [1][2][3]. Extensive studies have been investigated to estimate forest attributes from point clouds, including tree locations [4], heights [5][6][7], DBH [8], stem curves [9], crown widths [5,[10][11][12], crown base heights [13,14], wood volumes [15,16] and biomass [17][18][19][20]. Moreover, the improvement in LiDAR technology of higher pulse rates and the increasing LiDAR posting densities have provided better opportunities for obtaining forest data at a fine scale, and the forest inventory has transferred from an average forest stand scale to the individual tree level [21].…”
Section: Introductionmentioning
confidence: 99%